Dampak Sosial-Ekonomi Kemitraan KUD Tani Makmur dengan PT. Nestle Indonesia (Studi Kasus di Desa Kandang Tepus, Kecamatan Senduro, Kabupaten Lumajang) - ANDRIANI, LUKY AISYAH; WINDIA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Socio-Economic Impact Partnership KUD Tani Makmur with PT. Nestle Indonesia (Case Study in Kandang Tepus Village, Senduro Sub-District, Lumajang Regency) One form of relationship between subsystems in the agribusiness system is the relationship between dairy farmers, dairy cow cooperatives, and the Milk Processing Industry (IPS). One of the dairy cow milk cooperatives in partnership with IPS is the KUD Tani Makmur in Kandang Tepus Village, Senduro District, Lumajang Regency. KUD Tani Makmur in running his dairy cow business in partnership with PT. Nestle Indonesia.The partnership between KUD Tani Makmur and Nestle is contractual, in which this partnership impacts socially and economically for cooperatives. The purpose of this study was to determine the social and economic impacts of KUD Tani Makmur because they partnered with Nestle.The research method used for social impact is qualitative. Whereas for economic impacts quantitative analysis and trend analysis are used. The results of the analysis show that there is a change in knowledge, attitudes, and actions of cooperative employees and members. This change is positive. In addition, there are changes in positive social values and norms and institutions. The economic impact obtained is also positive, the cooperative has increased income, the number of members of the cooperative, the development of physical cooperatives. The SHU obtained by cooperatives in the 2013-2016 period fluctuated, which in 2015 experienced a decline. This extension is due to the lack of proper implementation of cooperative strategies in dealing with competitors. The positive impact of social and economic needs to be maintained, while to overcome competitors need to know the weaknesses and strengths of competitors so as not to implement a strategy that is inappropriate.